Origins of Adulthood Personality: The Role of Adverse Childhood Experiences - Jason M. Fletcher; Stefanie Schurer (Institute of Labor Economics (IZA), 2017)
We test whether adverse childhood experiences exposure to parental maltreatment and its indirect effect on health are associated with age 30 personality traits. We use rich longitudinal data from a large, representative cohort of young US Americans and exploit differences across siblings to control for the confounding influences of shared environmental and genetic factors. We find that maltreatment experiences are significantly and robustly associated with neuroticism, conscientiousness, and openness to experience, but not with agreeableness and extraversion. High levels of neuroticism are linked to sexual abuse and neglect; low levels of conscientiousness and openness to experience are linked to parental neglect. The estimated associations are significantly reduced in magnitude when controlling for physical or mental health, suggesting that adolescent health could be one important pathway via which maltreatment affects adulthood personality. Maltreatment experiences, in combination with their health effects, explain a significant fraction of the relationship between adulthood conscientiousness and earnings or human capital. Our findings provide a possible explanation for why personality traits are important predictors of adulthood labor market outcomes.
Keywords: J24; J13; I0; 330; human capital; noncognitive skills; Big Five personality traits; adverse childhood experiences; maltreatment; Add Health; siblings-fixed effects